SELECTIVE CHLORIDE LEACHING OF PALLADIUM FROM γ-Al₂O₃-BASED CATALYSTS: THERMODYNAMIC JUSTIFICATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The paper examines the thermodynamic and physicochemical foundations of the selective recovery of palladium from spent γ-Al₂O₃-based catalysts using the chloride leaching system HCl–NaOCl. It is shown that the combination of the oxidative action of sodium hypochlorite and the ability of palladium to form stable chloride complexes ensures a high degree of Pd recovery (95–98%) while preserving the structural integrity of the alumina support. The standard Gibbs free energy of the palladium oxidation reaction was calculated, confirming the thermodynamic spontaneity of the process. The obtained conclusions are consistent with experimental data and the analysis of electrochemical stability diagrams.